2006
DOI: 10.1097/00000542-200603000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay of Index Calculation

Abstract: The time delays of the tested indices may limit their value in prevention of recall of intraoperative events. Furthermore, different latencies for decreasing and increasing values may indicate a limitation of these monitors for pharmacodynamic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…Zhang determined the effects of propofol using AAI and BIS on the same population and obtained K e0 values of 0.64 and 1.87 min −1 , respectively. 21) Four factors could lead to such differences in K e0 . First, commonly used EEG-derived parameters cannot simultaneously reflect the effects of drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang determined the effects of propofol using AAI and BIS on the same population and obtained K e0 values of 0.64 and 1.87 min −1 , respectively. 21) Four factors could lead to such differences in K e0 . First, commonly used EEG-derived parameters cannot simultaneously reflect the effects of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that AAI or BIS values could not provide evident minimum recordings in some patients because of disturbances. 21) Finally, the Tpeak approach can only fit one dataset because of the three reasons discussed above. If the unique data are inaccurate, the values of K e0 are unreliable.…”
Section: Relationship Between K E0 and Agementioning
confidence: 99%
“…The BIS Index is updated every one second. The BIS trend is updated every 10 s. Time delay of index calculation for the Cerebral State Index, the Bispectral Index, and the Narcotrend Index was studied by Pilge et al [19]. In this paper, we apply the Lagrange method for monitoring the DoA on real signals.…”
Section: Monitor the Depth Of Anaesthesia Using Lagrange Methodsmentioning
confidence: 99%
“…By using spectral power, or parameters derived from it, as key parameters, the monitoring systems may dismiss signal information content by neglecting the phase component of the signals' frequency and only exploiting information from the amplitude spectrum (Callegaro, 2012). Further, the devices susceptibility to muscle activity (Messner et al, 2003; Schuller et al, 2015), especially by including high EEG frequencies as well as the time delay, necessary for index calculation (Pilge et al, 2006; Zanner et al, 2009; Kreuzer et al, 2012) may present a limiting factor in performance to reliably track the anesthetic state.…”
Section: Eeg-based Monitoring Of the Level Of Consciousness: Commercimentioning
confidence: 99%